Organic Compounds Learning Game to Promote Twelve Graders' Academic Achievement and Attitudes toward Chemistry in Thai Islamic Private School - Roswanna Safkolam; Piyasiri Soontornnon Sinchai (Universitas Negeri Semarang, 2026)
Organic chemistry is a crucial subject in chemistry. Its abstract nature can make it difficult for students to understand. Learning games are an educational innovation that can improve learning outcomes and motivate students in chemistry. This study aims to develop and test the efficiency of a learning game on organic compounds, compare students' academic achievement before and after learning, and examine students' attitudes toward chemistry. A one-group pretest-posttest design was used. The participants were 19 Grade 12 students in an Islamic private school in Thailand, selected through purposive sampling. The research instruments included 1) a learning game on organic compounds, 2) an achievement test on organic compounds, 3) an attitude toward chemistry questionnaire, and 4) a semi-structured interview on attitudes toward chemistry. Data were analyzed using percentages relative to the efficiency criterion (E1/E2) of 75/75 percent, mean, and standard deviation, paired t-test, and qualitative data were analyzed using content analysis. The results showed that the learning game's efficiency was 78.95/80.79. The average post-learning achievement score was statistically significantly higher than the pre-learning score at the .05 level. The students' attitudes toward chemistry were highly positive (¯X = 3.65, S.D. = 0.33). The research supports game-based learning, highlighting that play lowers anxiety and increases engagement. It demonstrates that educational games can promote equity by assisting students, particularly low achievers, and by encouraging active learning in science classes. The study finds that game-based learning enhances upper secondary students' performance in chemistry and attitudes toward the subject. Educators are encouraged to integrate learning games into science lessons to create a more engaging, equitable, and student-focused environment.